2018
DOI: 10.1111/apce.12191
|View full text |Cite
|
Sign up to set email alerts
|

Nonunion Employee Representation: Theory and the German Experience With Mandated Works Councils

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 123 publications
1
31
0
2
Order By: Relevance
“…Works councils can be implemented by employees irrespective of union membership to coordinate a collective voice. Two arguments hypothesize a relationship between works councils and collective bargaining participation (Jirjahn and Smith ): First, works councils can express the employees’ collective interest for remuneration by a collective contract. Second, empirical studies show that works councils are more effective in fostering productivity in the presence of a collective bargaining contract (Hübler and Jirjahn ), which should be of the employer's interest.…”
Section: Resultsmentioning
confidence: 99%
“…Works councils can be implemented by employees irrespective of union membership to coordinate a collective voice. Two arguments hypothesize a relationship between works councils and collective bargaining participation (Jirjahn and Smith ): First, works councils can express the employees’ collective interest for remuneration by a collective contract. Second, empirical studies show that works councils are more effective in fostering productivity in the presence of a collective bargaining contract (Hübler and Jirjahn ), which should be of the employer's interest.…”
Section: Resultsmentioning
confidence: 99%
“…We also examine whether the relationship between works councils and WHP depends on circumstances and type of firm. Previous research on the productivity effects of works councils has shown that the functioning of establishment-level codetermination can depend on moderating factors (Jirjahn and Smith 2018a). However, usually only one single factor is considered whereby the moderating factor analyzed varies across studies.…”
Section: Introductionmentioning
confidence: 99%
“…Economists have shown strong interest in German works councils. This is documented by a rapidly growing literature of econometric studies on the consequences of this institution (Jirjahn and Smith 2018a). The econometric studies have examined the influence of works councils on outcome variables such as wages, personnel turnover, job satisfaction, productivity, profitability, and innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Auf der anderen Seite kann der Betriebsrat danach streben, die Unternehmensgewinne zugunsten der Arbeitnehmer umzuverteilen. Das kann zu Konfl ikten führen (Stettes, 2010;Jirjahn und Smith, 2017). Empirische Untersuchungen für Deutschland kommen zu dem Ergebnis, dass die betriebliche Mitbestimmung für Unternehmen wie Arbeitnehmer zu einem Mehrwert (Winwin-Situation) führen kann.…”
Section: Betriebliche Mitbestimmung Und Partizipation Heuteunclassified
“…Empirische Untersuchungen für Deutschland kommen zu dem Ergebnis, dass die betriebliche Mitbestimmung für Unternehmen wie Arbeitnehmer zu einem Mehrwert (Winwin-Situation) führen kann. Das hängt allerdings entscheidend davon ab, ob das Management der Institution "Betriebsrat" aufgeschlossen gegenübersteht und beide Seiten miteinander kooperieren (Jirjahn und Smith, 2017). Wichtig ist dabei, Probleme frühzeitig zu lokalisieren und einen Konsens mit dauerhaften Lösungen herzustellen (Niedenhoff, 2020, 53).…”
Section: Betriebliche Mitbestimmung Und Partizipation Heuteunclassified